Polyphenols in Ruminant Nutrition and Their Effects on Reproduction - Drago Bešlo; Gloria Došlić; Dejan Agić; Vesna Rastija; Marcela Šperanda; Vesna Gantner; Bono Lučić (MDPI AG, 2022)
The feeding of domestic animals with diets in which polyphenols are present is increasingly attracting the attention of nutritionists and scientists. This review summarizes the knowledge regarding polyphenols' possible positive and negative effects and their bioavailability. The bioavailability of substances is a prerequisite for any postabsorption effect in vivo. Positive and negative properties have been confirmed in previous studies on the diets of domestic animals rich in polyphenols, such as secondary metabolites of plants. Free radicals are formed in every organism, leading to oxidative stress. Free radicals are highly reactive molecules and can react in cells with macromolecules and can cause damage, including in reproductive cells. Some polyphenols at specific concentrations have antioxidant properties that positively affect animal reproduction by improving the quality of male and female gametes. The intake of phytoestrogens that mimic estrogen function can induce various pathological conditions in the female reproductive tract, including ovarian, fallopian, and uterine dysfunction. The metabolism of genistein and daidzein yields the metabolites equol and p-phenyl-phenol, leading to a decline in cow fertilization. The findings so far confirm that numerous questions still need to be answered. This review points out the importance of using polyphenols that have both benificial and some unfavorable properties in specific diets.